The digital art technique manual for illustrators & artists : the essential guide to creating digital illustration and artworks using Photoshop, Illustrator, and other software - Lardner, Joel; Roberts, Paul (Barron's, 2012)
"This books shows you how to use the most common digital art software programs that have been designed specifically for artists and illustrators"--Page 4 of cover.